2002
DOI: 10.1152/ajpregu.00233.2002
|View full text |Cite
|
Sign up to set email alerts
|

Disinhibition of female sexual behavior by a CRH receptor antagonist in Syrian hamsters

Abstract: Several conditions that inhibit female sexual behavior are thought to be associated with altered corticotropin-releasing hormone (CRH) activity in the brain. The present experiments examined the hypothesis that endogenous CRH receptor signaling mediates the inhibition of estrous behavior by undernutrition and in other instances of sexual dysfunction. Intracerebroventricular (ICV) infusion of CRH or urocortin inhibited estrous behavior in ovariectomized steroid-primed hamsters. Conversely, ICV infusion of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 37 publications
(57 reference statements)
1
30
0
Order By: Relevance
“…We found that ICV treatment with doses of CRH or urocortin 1 that inhibited sexual receptivity in hamsters also activated the HPA axis. However, restraint stress, which also activated the HPA axis, had no effect at all on hamster estrous behavior (114).…”
Section: What About Stress?mentioning
confidence: 85%
See 3 more Smart Citations
“…We found that ICV treatment with doses of CRH or urocortin 1 that inhibited sexual receptivity in hamsters also activated the HPA axis. However, restraint stress, which also activated the HPA axis, had no effect at all on hamster estrous behavior (114).…”
Section: What About Stress?mentioning
confidence: 85%
“…Furthermore, astressin rapidly (Ͻ30 min) reverses the established inhibition of sexual receptivity by food deprivation ( Fig. 13) (114). Thus the peptides seem to act far too quickly to depend on changes in steroid receptor levels.…”
Section: Control Of Estrous Behaviormentioning
confidence: 93%
See 2 more Smart Citations
“…Acute stress in rats was shown to result in a short-term hypophagia and a long-term reduction in the rate of weight gain (17). Undernutrition causes inhibition of estrous behavior in female Syrian hamsters, and this was shown to involve activation of CRH receptors as a final step (21). Similar to leptin, insulin conveys adi-posity-related signals to the brain (11,35,38).…”
mentioning
confidence: 99%